ICLK2016: RAISING THE STANDARDS OF UNIVERSAL HERITAGE THROUGH LOCAL KNOWLEDGE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 27 July 2016 – Local Knowledge relates to the knowledge of a certain community which has undergone progress through time, in ensuring the longevity and sustainability of the unique heritage.